The use of electronic health and social care services in urban and rural areas in Finland - Vehko, Tuulikki; Kyytsönen, Maiju; Ikonen, Jonna; Koskela, Timo; Kainiemi, Emma; Parikka, Suvi (Finnish Journal of eHealth and eWelfare, 2022)
Several health policy goals have been outlined for electronic services in sparsely populated Western countries. Social and health care services may be implemented as electronic services, where applicable. However, the use of electronic services requires the necessary instruments, skills and service provision. We investigated the use of electronic services in health care among the adult population in different areas in Finland. The electronic services included contacts with a doctor, registered nurse or social worker by video or by chat. The study is based on responses from randomly selected individuals aged 20 to 99 (n=28 199; participation rate: 46%) at FinSote. The results are presented as non-adjusted and adjusted proportions. We used the seven-class urban–rural classification provided by the Finnish Environment Institute. We report the results for the working-age population (aged 20 to 64) and for the retired population (aged 65 to 99). In urban areas, the use of electronic services for health or social care was higher than in rural areas. Electronic service use among the working-age population was 39% among those living in inner urban areas compared with 25% of those living in sparsely populated rural areas. The use of electronic services was lower (only 13% and 8% for inner urban areas and sparsely populated rural areas respectively) among those of pensionable age. While 86% of the working-age population in the outer urban area and 75% of those living in local centres in rural areas reported that at least one electronic contact replaced a face-to-face visit, the proportion of those of pensionable age was lower: 70% in the inner urban areas and 54% in sparsely populated rural areas. Among those members of the population that have used health and social care services within a year, the use of electronic services was relatively high. The use of electronic services was more common in urban areas compared with sparsely populated rural areas. Respondents who had used social and health care services electronically more often stated that the electronic service use replaced the face-to-face visit. The working-aged respondents used electronic services more often than the older respondents. In the future, more information is needed on the supply of electronic services in the public social and health care services available in different regions. For many, the use of electronic services has become everyday life. How to keep the instruments accessible to everyone, how to improve skills and how to support the use of electronic services are challenges that need to be addressed by both social and health policy and employment and education policy.